2016
DOI: 10.1002/etc.3362
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mt:egfp transgenic zebrafish biosensor for the detection of aquatic zinc and cadmium

Abstract: Zebrafish embryo toxicity testing has become a popular method for detecting environmental pollutions. However, the present research showed that zebrafish embryos exhibited no visible paramorphia, malformation, or mortality when exposed to heavy metals in a range above environmental standard limits, indicating that zebrafish embryos are an imprecise model for monitoring environmental heavy metals concentrations above regulatory limits. Aiming to obtain a biosensor for aquatic heavy metals, a metal-sensitive vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Mitoxantrone hydrochloride (CAS: 70476-82-3, M6545) was purchased from Sigma. Mitoxantrone was dissolved in an E3 buffer (5 mM NaCl, 0.17 mM KCl, 0.33 mM CaCl 2 , 0.33 mM MgSO 4 ) to a final concentration of 1 g/L [ 62 ]. Stock solution was stored in the dark at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Mitoxantrone hydrochloride (CAS: 70476-82-3, M6545) was purchased from Sigma. Mitoxantrone was dissolved in an E3 buffer (5 mM NaCl, 0.17 mM KCl, 0.33 mM CaCl 2 , 0.33 mM MgSO 4 ) to a final concentration of 1 g/L [ 62 ]. Stock solution was stored in the dark at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Aiming to acquire a biosensor for aquatic heavy metals, transgenic zebrafish lines Tg (mt: EGFP) and Tg (MT‐Ia1: DsRed2) sensitive to aquatic Zn 2+ , Cd 2+ and Hg 2+ , Cd 2+ , Cu 2+ were obtained (Liu et al . 2016). Recently, Moon et al .…”
Section: Genetically Modified Fish Applicationsmentioning
confidence: 99%
“…The expression of GFP in the zebrafish using the gonad aromatase (cyp19a1a) promoter can be used to assay for endocrine-disrupting chemicals (EDCs) in aquatic environments (Hinfray et al 2018). Aiming to acquire a biosensor for aquatic heavy metals, transgenic zebrafish lines Tg (mt: EGFP) and Tg (MT-Ia1: DsRed2) sensitive to aquatic Zn 2+ , Cd 2+ and Hg 2+ , Cd 2+ , Cu 2+ were obtained (Liu et al 2016). Recently, Moon et al (2020) provided a method for joint assessment of river pollution using Tg (fli1: GFP) and Tg (HuC: eGFP) zebrafish.…”
Section: Environmental Toxicology Monitoringmentioning
confidence: 99%
“…The Tg(mt:egfp) transgenic zebrafish expresses enhanced green fluorescent protein (EGFP) under the transcriptional control of the metal-responsive metallothionein promoter. This line can be used as a reporter for aquatic zinc and cadmium (Liu, Yan, et al, 2016). Recent data had shown that 10 days postfertilization (dpf) zebrafish larvae did not show significant developmental abnormalities even when exposed to levels of heavy metals that exceeded current regulatory limits by 10- or 70-fold for zinc and cadmium, respectively; however, transgene activity was detected following 24 h of exposure to zinc at the current regulatory limit and cadmium at twice the current regulatory limit.…”
Section: Zebrafish: Testing the Waters For Toxicantsmentioning
confidence: 99%
“…Recent data had shown that 10 days postfertilization (dpf) zebrafish larvae did not show significant developmental abnormalities even when exposed to levels of heavy metals that exceeded current regulatory limits by 10- or 70-fold for zinc and cadmium, respectively; however, transgene activity was detected following 24 h of exposure to zinc at the current regulatory limit and cadmium at twice the current regulatory limit. Use of the Tg(mt:egfp) zebrafish line provides an advance in the field as it provides a more robust readout for the presence of elevated levels of heavy metals (Liu, Yan, et al, 2016). This is useful, as exposure to a number of different metals is associated with neurodevelopmental deficits.…”
Section: Zebrafish: Testing the Waters For Toxicantsmentioning
confidence: 99%